2023
DOI: 10.1002/prep.202300161
|View full text |Cite
|
Sign up to set email alerts
|

Representation of live‐fire energetic residues from insensitive mortar munitions using command‐detonation testing

Samuel A. Beal,
Matthew F. Bigl,
Charles A. Ramsey
et al.

Abstract: Command (i. e., static) detonation is critical for testing munitions early in the acquisition process, however its representation of energetic residues produced during live fire has not yet been assessed. Here we measured energetic residue deposition rates on snow from live fire of 60 mm and 81 mm IMX‐104 mortar munitions and then compared results with previous command‐detonation tests of the same munitions. Mean live‐fire deposition rates of IMX‐104 compounds were: 3800 mg NTO, 34 mg DNAN, 12 mg RDX, and 1.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…2,4-Dinitroanisole (DNAN) is one of the most commonly used organic energetic compounds among the insensitive munitions (IM) evaluated by the defense industry as replacements for conventional legacy explosives. , Due to its excellent detonation characteristics, low melting point, and lower susceptibility to shock and accidental explosion, DNAN has gained popularity for its use in melt-pour IM formulations. Over 900,000 pounds of DNAN were manufactured in the U.S. in 2019, and production is expected to increase. DNAN may be released from wastewater discharge of formulation manufacturing or munitions load-and-pack (LAP) assembly sites, with reported DNAN concentrations at 128–137 μg L –1 from LAP wastewater effluent. Additionally, live-fire training deposits explosives on military training ranges due to incomplete post-detonation. , Previous studies found that post-detonation residues of DNAN accounted for 0.006–0.5% of its filler mass in IM projectiles. , Due to the relatively low adsorption of DNAN in soil (i.e., K D = 0.6–9.1 L kg –1 ), DNAN can readily enter groundwater and undergo long-range transport. Although limited information is available on its human health risks, DNAN is known to be toxic to aquatic organisms, fishes, earthworms, and mammals. Thus, there is an urgent need to develop effective strategies to retain and degrade DNAN and similar compounds present in sources of contamination to prevent their adverse effects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,4-Dinitroanisole (DNAN) is one of the most commonly used organic energetic compounds among the insensitive munitions (IM) evaluated by the defense industry as replacements for conventional legacy explosives. , Due to its excellent detonation characteristics, low melting point, and lower susceptibility to shock and accidental explosion, DNAN has gained popularity for its use in melt-pour IM formulations. Over 900,000 pounds of DNAN were manufactured in the U.S. in 2019, and production is expected to increase. DNAN may be released from wastewater discharge of formulation manufacturing or munitions load-and-pack (LAP) assembly sites, with reported DNAN concentrations at 128–137 μg L –1 from LAP wastewater effluent. Additionally, live-fire training deposits explosives on military training ranges due to incomplete post-detonation. , Previous studies found that post-detonation residues of DNAN accounted for 0.006–0.5% of its filler mass in IM projectiles. , Due to the relatively low adsorption of DNAN in soil (i.e., K D = 0.6–9.1 L kg –1 ), DNAN can readily enter groundwater and undergo long-range transport. Although limited information is available on its human health risks, DNAN is known to be toxic to aquatic organisms, fishes, earthworms, and mammals. Thus, there is an urgent need to develop effective strategies to retain and degrade DNAN and similar compounds present in sources of contamination to prevent their adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…7−10 Additionally, live-fire training deposits explosives on military training ranges due to incomplete post-detonation. 11,12 Previous studies found that post-detonation residues of DNAN accounted for 0.006−0.5% of its filler mass in IM projectiles. 11,13 Due to the relatively low adsorption of DNAN in soil (i.e., K D = 0.6−9.1 L kg −1 ), DNAN can readily enter groundwater and undergo long-range transport.…”
mentioning
confidence: 99%
See 1 more Smart Citation